Therapeutic Ultrasound as a Treatment Modality for Physiological and Pathological Ageing Including Alzheimer's Disease - Jürgen Götz; Gina Richter-Stretton; Esteban Cruz (MDPI AG, 2021)
Physiological and pathological ageing (as exemplified by Alzheimer's disease, AD) are characterized by a progressive decline that also includes cognition. How this decline can be slowed or even reversed is a critical question. Here, we discuss therapeutic ultrasound as a novel modality to achieve this goal. In our studies, we explored three fundamental strategies, (i) scanning ultrasound on its own (SUSonly), (ii) therapeutic ultrasound in concert with intravenously injected microbubbles (which transiently opens the blood-brain barrier, SUS+MB), and (iii) SUS+MB in combination with therapeutic antibodies (SUS+MB+mAb). These studies show SUS+MB effectively clears amyloid and restores memory in amyloid-depositing mice and partially clears Tau and ameliorates memory impairments in Tau transgenic mice, with additional improvements found in combination trials (SUS+MB+mAb). Interestingly, both SUSonly and SUS+MB restored the induction of long-term potentiation (LTP, electrophysiological correlate of memory) in senescent wild-type mice. Both lead to increased neurogenesis, and SUSonly, in particular, resulted in improved spatial memory. We discuss these findings side-by-side with our findings obtained in AD mouse models. We conclude that therapeutic ultrasound is a non-invasive, pleiotropic modality that may present a treatment option not only for AD but also for enhancing cognition in physiological ageing.